Klasterisasi Wilayah Rentan Bencana Alam Berupa Gerakan Tanah Dan Gempa Bumi Di Indonesia - I Nyoman Setiawan; Dewi Krismawati; Setia Pramana; Erwin Tanur (Politeknik Statistika STIS, 2022)
Indonesia is one of the countries prone to natural disasters, such as soil movements and earthquakes. The people of Indonesia have felt various kinds of impacts caused by the disaster, both in the form of losing their jobs, their homes, and even their beloved family members. However, this impact can certainly be minimized with good disaster management. Therefore, the author focuses on the clustering of earthquake-prone areas in Indonesia using Density-based Spatial Clustering of Application with Noise (DBSCAN), Common Nearest Neighbor Clustering (CNN), and K-Medoids. The results of the clustering show that the soil movement-prone cluster formed from the DBSCAN algorithm is centered on the islands of Java and Bali, as well as along the western part of North Sumatra to Lampung, while the earthquake-prone areas formed from the K-Medoids algorithm are spread over the area traversed by the Pacific Ring of Fire.